Developing Assessment Instruments of PISA Model to Measure Students Problem-Solving Skills and Scientific Literacy in Junior High Schools - Rosana, Dadan; Widodo, Eko; Setianingsih, Wita; Setyawarno, Didik (Universitas Syiah Kuala, 2020)
This study aims at producing an assessment instrument of the PISA model to measure students problem-solving skills and scientific literacy in junior high schools that are valid, practical, and having potential effects. This research employed the design of development studies. The analysis used the Item Response Theory (IRT) Rasch model based on the junior high school students' responses to the developed PISA assessment instrument on natural science subjects. The result of this study was a test set of PISA model for the material of Vibration, Wave, and Sound consisting of 40 items. The test was valid in terms of content, constructs, and language according to the expert assessment, and practical based on small group trials. It also had a potential effect based on the students answers and questionnaires results in the field test. The qualitative analysis showed that the developed test had several potential effects, i.e. the development of students' problem-solving skills and scientific literacy so that they gained a relatively high ability to solve a test with the PISA model. The results of quantitative analysis through field test trials showed that there was a significant effect from the application of the PISA model test to enhance students scientific literacy and problem-solving skills in the junior high school with the Sig. value of 0.000 which was less than the significance level of 0.05 ( = 5%).